The sustainability of the bluefin tuna resource: A fishery and aquaculture integrated challenge - Sudre M. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
This short introduction deals with the various directions in which fisheries and aquaculture could harmonize in the future to provide a sustainable fishery for bluefin tuna. The pertinent questions are proposed which cover not only the fisheries aspects but also the socio-economic policy to be considered for the future.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)